2021
DOI: 10.3390/jtaer16040046
|View full text |Cite
|
Sign up to set email alerts
|

Proximity, Familiarity or Congruency? What Influences Memory of Brand Placement in Videogames

Abstract: Brand placement in videogames consists in integrating various brands that are not intrusive to give a feeling of reality to the context, as such increasing awareness and recognition of the brand in the mind of the consumer. The goal of this study is to ascertain if brand position, familiarity and congruency influence memorization of brands presented in a racing videogame. An experimental design 2 (position: prominent or subtle) × 2 (congruency: yes or no) × 2 (familiar: yes or no) was used in a sample of 117 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(101 reference statements)
0
2
0
6
Order By: Relevance
“…One advantage of advertising in video games is that it cannot be avoided, which means that players are unavoidably exposed to it. According to research by [10] that evaluated performance between children who played video games and those who did not, it was found that the brains of the former group showed greater activity in regions associated with attention and memory; the researchers believe that this is because video games, having more cognitively demanding tasks, improved brain performance in these areas (as cited in National Institute on Drug Abuse).…”
Section: In-game Advertisingmentioning
confidence: 99%
“…One advantage of advertising in video games is that it cannot be avoided, which means that players are unavoidably exposed to it. According to research by [10] that evaluated performance between children who played video games and those who did not, it was found that the brains of the former group showed greater activity in regions associated with attention and memory; the researchers believe that this is because video games, having more cognitively demanding tasks, improved brain performance in these areas (as cited in National Institute on Drug Abuse).…”
Section: In-game Advertisingmentioning
confidence: 99%
“…A name, symbol, or combination of both is referred to as a brand when describing or identifying one product or service from others. While awareness refers to the impact a brand has on consumers' perceptions [21]. Brand awareness, as described by Aaker (1996), is the capacity of consumers to recognize and recall that a brand belongs to a given category of items [22].…”
Section: Introductionmentioning
confidence: 99%
“…Respecto al objetivo principal de esta estrategia publicitaria, es la influencia positiva que puede causar en la actitud y comportamiento del televidente en los diversos formatos en el que se desarrolla (Aliagas et al, 2021;Boerman et al, 2021). Además de las ventajas como el despertar de actitudes positivas al presentarse en un programa de entretenimiento, según lo manifestado por Chan & Lowe (2021) o la reducción del zapping, al no notar que están expuestos ante un anuncio (Ibarra, 2018).…”
Section: Product Placementunclassified
“…Además de las ventajas como el despertar de actitudes positivas al presentarse en un programa de entretenimiento, según lo manifestado por Chan & Lowe (2021) o la reducción del zapping, al no notar que están expuestos ante un anuncio (Ibarra, 2018). Cabe mencionar que para obtener los resultados deseados al momento de la ejecución del product placement, las marcas que desean invertir en un programa o serie, primero deben estar seguros de que su marca se encuentre relacionada con el tema central alrededor del cual gira el programa, esto a fin de no pasar desapercibida o ser rechazada por el público (Aliagas et al, 2021;Chan, 2020).…”
Section: Product Placementunclassified
See 1 more Smart Citation